PCNA-mediated stabilization of E3 ligase RFWD3 at the replication fork is essential for DNA replication - Lin, Yo-Chuen (Proc Natl Acad Sci U S A, 2018)
RING finger and WD repeat domain-containing protein 3 (RFWD3) is an E3 ligase known to facilitate homologous recombination by removing replication protein A (RPA) and RAD51 from DNA damage sites. Further, RPA-mediated recruitment of RFWD3 to stalled replication forks is essential for interstrand cross-link repair. Here, we report that in unperturbed human cells, RFWD3 localizes at replication forks and associates with proliferating cell nuclear antigen (PCNA) via its PCNA-interacting protein (PIP) motif. PCNA association is critical for the stability of RFWD3 and for DNA replication. Cells lacking RFWD3 show slower fork progression, a prolonged S phase, and an increase in the loading of several replication-fork components on the chromatin. These findings all point to increased frequency of stalled forks in the absence of RFWD3. The S-phase defect is rescued by WT RFWD3, but not by the PIP mutant, suggesting that the interaction of RFWD3 with PCNA is critical for DNA replication. Finally, we observe reduced ubiquitination of RPA in cells lacking RFWD3. We conclude that the stabilization of RFWD3 by PCNA at the replication fork enables the polyubiquitination of RPA and its subsequent degradation for proper DNA replication.